UN SOFTWARE COMO COMPLEMENTO PARA EL ANALISIS DE LA PRACTICA EXPERIMENTAL DEL PENDULO - OLGA LUCIA CASTIBLANCO ABRIL; DIEGO FABIAN VIZCAINO AREVALO (Universidad Distrital Francisco José de Caldas, 2010)
We present an application for the software "Geogebra" as a tool that it allow to study in depth a physical phenomenon, for this case the study about simple and coupled pendulum. The fundamental idea is to extract the major profit from the analysis by means of graphs that are very difficult to obtain if they become taking information directly of the experience, in order to this goal is necessary to consider reflections for re thinking the speech with which usually the topic is presented, allowing students for exposes his confusions or doubts. The aim is not offer exactly activities sequences in order that the teacher develops the class, but to offer elements for the teacher could re create his educational work.